FORMULASI GREEN TEA LEAVES (Camellia sinensis L.) GEL WITH THE COMBINATION OF METHYL CELLULOSA AND CARBOPOL 940 AS ANTIOXIDANT AGENT - Ariis Purwanto; Irfan Zamzani (JCPS (Journal of Current Pharmaceutical Sciences), 2020)
Green tea extract can be used as an antioxidant because it contains catechins in massive, the use of this extract in direct application can an unpractical, so it was made in the form of gel. The addition of the methylcellulose and carbopol were used as the basis of the gel formation. The aim of this research was to get the gel optimum formula of the green tea extract using two addition substances they were methylcellulose and carbopol. The green tea extract was obtained by maceration using ethanol 70% then it was evaporated to obtain concentrated extract. The gel made in four formulas based. The gel produced were tested for physical characteristics of organoleptic, viscosity, spreading ability, the time of sticking, and activity of antioxidant. The optimum formula based on parameters of physical characteristics of the gel; they are viscosity, the spreading ability, the time of sticking. The results showed that the tea leaf extract can be made as a gel which has anti-toxic agents. The IC50 value in the four tea leaf extract gel formulas can be a very strong antioxidant agent (IC50 value <50).